Multivariate Analysis of Risk Factors for Destructive Behavior in Children in Indonesia - Nany Hairunisa; Husnun Amalia; Agnes Tineke Waney Rorong; Yasmine Mashabi; Muhammad Amru Hammam El Putra; Asrenee Ab. Razak (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Conduct disorders pose a significant global burden, affecting an estimated 5.75 million children and adolescents, especially boys. Conduct disorders involve repetitive behaviors that violate others rights and can jeopardize normal relationships between children and those around them. Major behavioral issues in children often occur in both school and family settings and are closely linked to the roles of parents and teachers as educators and guides. Additionally, children at a young age are highly curious and eager to explore new things; the rapid growth of technology introduces new challenges for them. Without parental guidance, considering factors such as parenting styles, education level, socioeconomic status, and occupation, children's social lives may be significantly impacted. This study aims to analyze various risk factors associated with disruptive behavior among children in Indonesia. This cross-sectional study used a guided questionnaire involving 301 parents/guardians of children aged 2-5 years. In this regard, the researchers were assisted by data enumerators residing at the study site. Data collection was conducted in two regions in Indonesia, Greater Jabodetabek (Jabodetabek) and Aceh, from October 2024 to January 2025. Bivariate analyses were performed using the Chi-square test, followed by binary logistic regression to determine factors independently associated with disruptive behavior. Bivariate analysis indicated that type of content (p = 0.017), screen time allocation (p = 0.018), and parenting pattern (p = 0.043) were significantly associated with disruptive behavior, while other variables such as parental education, domicile, occupation, marital status, and child’s age or gender showed no significant relationships. In the multivariate model, only type of content remained a significant predictor (p = 0.018). The study highlights that the quality of media content, rather than the amount of screen time, plays a key role in the emergence of disruptive behavior among children. Parental guidance and the selection of educational media content are essential preventive strategies. Interventions focusing on digital literacy and positive parenting may help mitigate the risk of behavioral problems in early childhood.